Upaya Amerika Serikat dalam Kapitalisasi Penambangan Asteroid Periode 2010 – 2020 - Thomas Adhityo Pramono; Reni Windiani; Satwika Paramasatya (Journal of International Relations Diponegoro, 2021)
Since decades ago, space has been one of the final frontiers for any nation to promote their technological achievements. The race to reach the space, which started since the cold war, now has started to entering a whole new level. Right now, those nations not only competing on their own technological advancement, but also, they’ve started trying explore and exploits the Space itself. Many big nations have started to improve their tech to grab this new area fulfilled with lot of economic potential. Using the Offensive Realism as its theoretical foundation, this research tries to analyze United States policy regarding the Outer Space, especially seeing United States trying to be the key player. The establishment of Military instances which focused on outer space and also the creation of law about outer space commercialization become the main proof that United States trying to dominate the leadership on this new Space Race.